The Cenozoic of Nepal: mountain elevation and vertebrate evolution - West, R. M. (Journal of Nepal Geological Society, 1996)
The Cenozoic of Nepal was a time of great activity, in terms of both the establishment and uplift of the Himalaya and the development of a vertebrate fauna which changed through time in response to the environmental events caused by the elevation of the mountains. Field work conducted over the past twenty years has generated a body of data which brings together palaeontological, ecological, and tectonic interpretations of the Cenozoic history of Nepal Himalaya. Palaeontological data from Nepal are geographically limited. At this time, the early Cenozoic is represented by modest marine and terrestrial mammal remains found near Tansen. The middle and late Cenozoic is also documented from abundant materials found in the Siwaliks in a broad band of Sub-Himalayan sedimentary rocks between Butwal and Nepalganj and north of Jaleswar. Ice Age in Nepal may be interpreted from several Pleistocene localities in the Kathmandu Valley. Nepal's Cenozoic palaeoenvironments are interpreted in large from the fossils found in the areas mentioned above, by analogy to India and Pakistan, and by study of the sedimentology of the enclosing rocks. It is possible to document the arrival of the Indian tectonic plate in South Asia in the early Cenozoic using palaeontologic, sedimentologic and tectonic data. At this time the broad open seaway (the remnant of Tethys) which occupied much of Nepal until the early Cenozoic closed and terrestrial communication with other areas became possible. By the middle Cenozoic, Nepal was the site of major erosional deposition from the rising Himalaya. This palaeoenvironment is indicated by both the terrestrial elastic sedimentary rocks which dominate the Nepal middle and late Cenozoic sequences as well as by the particular vertebrate taxa which have been recovered from the Siwaliks in western Nepal. Nepal's Pleistocene was a time of cool and dry environments; Kathmandu Valley deposits have yielded vertebrate remains which are indicative of this environment. Of particular interest are efforts to relate Himalayan Cenozoic tectonics to the palaeobiological record of Nepalese environments. There are strong indications that the primary elevation of the Himalaya was a mid to late Cenozoic event; this correlates well with the environmental evidence from the fossil assemblages. This paper is devoted to review of palaeontologic, sedimentologic and tectonic data which are used to interpret the Cenozoic history of Nepal Himalaya.